RNA Editing of Serotonin 2C Receptor and Alcohol Intake - Tanaka, Masaki; Watanabe, Yoshihisa (Frontiers in Neuroscience, 2020)
Serotonin 2C receptor (5-HT2CR) belongs to the superfamily of seven transmembrane domain receptors coupled to G proteins (GPCR). It is broadly distributed in the central nervous system and its expression is relatively high in the limbic system including the amygdala, nucleus accumbens (NAc), hippocampus, and hypothalamus. Based on its expression patterns and numerous pharmacological studies, 5-HT2CR is thought to be involved in various brain functions including emotion, appetite, and motor behavior. Here, we review 5-HT2CR and its relationship with alcohol intake with a particular focus on the involvement of 5-HT2CR mRNA editing and its association with alcohol preference in mice. RNA editing is a post-transcriptional modification mechanism. In mammals, adenosine is converted to inosine by the deamination enzymes ADAR1 and ADAR2. 5-HT2CR is the only GPCR subjected to RNA editing within the coding region. It has five editing sites in exon 5 that encode the second intracellular loop. Consequently, three amino acids residues (I156, N158, and I160) of the unedited receptor (INI) may be altered to differently edited isoforms, resulting in a change of receptor activity such as 5-HT potency and G-protein coupling. 5-HT2CR in the NAc is involved in enhanced alcohol drinking after chronic alcohol exposure and alterations in 5-HT2CR mRNA editing is important in determining the alcohol preference using different strains of mice and genetically modified mice. RNA editing of this receptor may participate in the development of alcoholism.